Numerical solutions of forced convection boundary layer flow on a horizontal circular cylinder with Newtonian heating - Salleh, Mohd Zuki; Nazar, Roslinda; Md. Arifin, Norihan; Pop, Ioan (Universiti Putra Malaysia Press, 2011)
This study considers the steady forced convection boundary layer flow over a horizontal circular cylinder, generated by Newtonian heating in which the heat transfer from the surface is proportional to the local surface temperature. The governing boundary layer equations are first transformed into a system of nondimensional equations via the non-dimensional variables, and then into nonsimilar equations before they are solved numerically using a numerical scheme known as the Keller box method. Numerical solutions are obtained for the skin friction coefficient and the local wall temperature as well as the velocity and temperature profiles.